2021
DOI: 10.1042/bsr20200869
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ribosomal protein family in triple-negative breast cancer by bioinformatics analysis

Abstract: Triple-negative breast cancer (TNBC) accounts for ∼20% of all breast cancer (BC) cases. The management of TNBC represents a challenge due to its worse prognosis, heterogeneity and lack of targeted therapy. Moreover, its mechanisms are not fully clear. The aim of the study is to identify crucial genes between TNBC and non-TNBC for underlying targets for diagnostic and therapeutic methods of TNBC. The differentially expressed genes (DEGs) between TNBC and non-TNBC were selected from the Gene Expression Omnibus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 39 publications
(45 reference statements)
1
12
0
Order By: Relevance
“…Sun et al reported that RPL14(eL14) can rescue the progression role of miR-129-5p in cervical cancer cells [ 15 ]. In triple-negative breast cancer patients, the reduced expression of RPL14(eL14) was associated with lower survival rates [ 16 ]. Thus, literatures suggest that RPL14(eL14) is related to tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al reported that RPL14(eL14) can rescue the progression role of miR-129-5p in cervical cancer cells [ 15 ]. In triple-negative breast cancer patients, the reduced expression of RPL14(eL14) was associated with lower survival rates [ 16 ]. Thus, literatures suggest that RPL14(eL14) is related to tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…3A ). Interestingly, low expression of ribosome-regulating genes including RPL11 was associated with a poor overall survival in triple-negative breast cancer patients [ 36 ]. Therefore, further work is necessary to determine the role of RPL11 in breast cancer and the consequences of its upregulation in anticancer effect of DATS.…”
Section: Discussionmentioning
confidence: 99%
“…At present, lots of studies on ribosomal proteins are related to cancer, and there is no study related to psoriasis. Ribosomal protein dysfunction is related to cancer, metabolic disorder and inflammation and ribosomal protein ubiquitination is a feedback mechanism of the body ( Wang W. et al, 2015 ; Lin et al, 2021 ). Our results show that the level of ubiquitinase decreases in psoriasis blood dryness syndrome, while ribosomal protein decreases in blood stasis syndrome, which may suggest that there are some connections and differences between the two syndrome types in inflammation and metabolism.…”
Section: Discussionmentioning
confidence: 99%